Economic Policy and Prospects in Iraq - Keith Crane; Block; Christopher Foote; Simon Gray (Federal Reserve Bank of Boston, 2004)
This paper describes the Coalition Provisional Authority's attempts to stabilize and reform Iraq's economy along market lines. It argues that while security concerns remain serious, Iraq's economy has not been crippled by violence. However, sustained economic growth will depend on whether Iraq's future leaders pursue the pro-market approaches the Coalition has advocated. If the Iraqi economy is to reach its potential, it will need to go even farther than the Coalition did, implementing reforms the Coalition did not pursue because of security concerns.
Keywords: 330; Wirtschaftspolitik; Wirtschaftsreform; Wirtschaftslage; Irak